Avaliação do Potencial de Descoloração de Corantes Azo por Lodo Granular Aeróbio. - Xavier, Renan da Silva (2023)
The azo dyes are essential products in the dyeing process of textile industries, However, they generate problems when not treated correctly, such as visual and organoleptic changes in water, thus hindering their use. Therefore, the search for adequate treatment is necessary, but the difficulty in treating these compounds, which require anaerobic and aerobic steps for complete mineralization, makes selecting of treatment difficult. The aerobic granular sludge (AGS) technology, which can perform aerobic and anaerobic steps in its system, is attractive. Thus, in the present work, the removal of azo dyes by AGS was evaluated, verifying its performance under different conditions, such as variation of the dye structure (Reactive Black 5 (RB5), Reactive Orange 16 (RO16) and Reactive Red 120 (RR120)), type of substrate (acetate, glucose, propionate and ethanol), presence of redox mediator (anthraquinone-2- sulfonate (AQS) and anthraquinone-2,6-disulfonate (AQDS)) and presence of alternative electron acceptors (sulfate and nitrate). 12-h batch tests were conducted using AGS, with 6 h of anaerobic phase and 6 h of aerobic phase. Concerning the substrates, the RB5 decolorization efficiencies ranged from 75% to 83%, where propionate provided the best performance. The addition of the mediators mainly impacted the kinetics of the reaction, however, with contrasting results, with AQDS performing similarly to the control, and at a specific concentration (25 μM), even worse. On the other hand, AQS led to better results overall, especially at 50 μM, when a kinetic constant 30% higher than that of the control and the assay with AQDS at 50 μM was obtained, indicating that it is the most recommendable mediator to accelerate the reduction of RB5. Different types of dyes showed that their different structures impact the removal process, with RR120 showing the worst result, with 14.4% without AQS and 25% with 50 μM AQDS. In contrast, RO16 had a high sensitivity to the mediator’s presence, with 48% removal without AQS and 97.1% with 50 μM of the mediator. The presence of sulfate inhibited the reduction of RB5, achieving a removal of only 60%, but AQS improved the decolorization, rising to 78.1%. In the presence of nitrate, the removal dropped considerably to 32.5%, an effect that was minimized with the supplementation of AQS, which improved the reduction of the dye to 47.6%. Therefore, the redox mediator can potentially minimize the inhibitory effect of preferential electron acceptors, such as sulfate and nitrate. In addition to these assays, a continuous experiment was performed in two AGS sequencing batch reactors (one control and one supplemented with RB5) in 41 days, divided into two stages: with and without AQS, to evaluate the impact of the presence of the dye and the AQS redox mediator on their performance and stability. The reactors presented high COD removal (>90%), indicating that neither the dye nor the mediator interfered in the removal of organic matter from the AGS. The sedimentability of the reactor with RB5 was unstable throughout the experiment, being, however, similar to the control reactor, indicating that the presence of RB5 and AQS were not responsible for this. As for nutrients, in both systems, ammonia removal averaged 98%, with a total nitrogen removal of 80%, while phosphorus removal was less than 30%, thus being independent of RB5 and AQS. Finally, the average color removal efficiency, without the presence of mediator, was close to 65%, increasing to 80% with the addition of AQS, which also positively impacted the system's stability.